2017
DOI: 10.1016/j.whi.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Do 72-Hour Waiting Periods and Two-Visit Requirements for Abortion Affect Women's Certainty? A Prospective Cohort Study

Abstract: Purpose: This paper examines how Utah's 72-hour waiting period and two-visit requirement influence women's certainty about their decision to have an abortion.Procedures: This study uses data from a prospective cohort study of 500 women who presented at an abortion information visit at four Utah family planning facilities. At the information visit, participants completed a baseline survey; three weeks later, they completed telephone interviews that assessed their pregnancy outcome, change in certainty, and an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Eight studies were randomized controlled trials, including two pilot studies (Sonalkar et al, 2017; Wu et al, 2012). Two studies used prospective cohort designs (Roberts et al, 2017; Veiga et al, 2011). Half of the trials recruited women undergoing surgical abortion (Chor et al, 2015; Guerrero et al, 2012; Veiga et al, 2011; Wilson et al, 2017; Wu et al, 2012), while other trials either included women having a medical abortion (Constant et al, 2014; Gerdts et al, 2020) or did not limit inclusion on type of abortion (Roberts et al, 2017; Sonalkar et al, 2017; Yu et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies were randomized controlled trials, including two pilot studies (Sonalkar et al, 2017; Wu et al, 2012). Two studies used prospective cohort designs (Roberts et al, 2017; Veiga et al, 2011). Half of the trials recruited women undergoing surgical abortion (Chor et al, 2015; Guerrero et al, 2012; Veiga et al, 2011; Wilson et al, 2017; Wu et al, 2012), while other trials either included women having a medical abortion (Constant et al, 2014; Gerdts et al, 2020) or did not limit inclusion on type of abortion (Roberts et al, 2017; Sonalkar et al, 2017; Yu et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Information intervention were defined as providing information or education related to abortion management (Constant et al, 2014; Gerdts et al, 2020), reproductive health skills or other health issues regarding abortion (Yu et al, 2010); specific strategies included messages by computer or telephone (Constant et al, 2014; Gerdts et al, 2020), and using printed materials and role‐play/group discussion (Yu et al, 2010). Mandatory policies were defined as mandated waiting or counseling requirements for women seeking abortion (Roberts et al, 2017; Sonalkar et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies indicate that compulsory waiting periods have no medical or practical relevance for women seeking abortion care; instead, they demean women's competency as decision makers . Most women seeking an abortion are not conflicted about their decision to obtain one and have chosen to have an abortion prior to making an appointment; waiting periods, studies have shown, have little impact on the decision‐making process . Indeed, the World Health Organization considers compulsory waiting periods to be a barrier to safe abortion access in the context of human rights …”
Section: Discussionmentioning
confidence: 99%
“…A majority of women in a study in Utah were certain of their decision to have an abortion when they presented for their abortion “information visit” and their certainty was resolute despite the information visit and a 72-hour waiting period. 64 The small minority whose certainty changed were conflicted before the beginning of the information visit. Roberts et al concluded that individualized counseling for the minority who are conflicted when they first attend seems more appropriate than universal requirements that create unnecessary hardships for women, the vast majority of whom have made their decision by the time they present for abortion.…”
Section: Abortionmentioning
confidence: 99%